2022
DOI: 10.1002/cphc.202200526
|View full text |Cite
|
Sign up to set email alerts
|

DFT Insights into the Variety in the Coordination Modes of the Equatorial Halides in [Au13Ag12(PR3)10X8]+ (X=Cl/Br) Clusters

Abstract: The bonding character within metal nanoclusters represents an intriguing topic, shedding light on the inherent driving force for the packing preference in nanomaterials. Herein, density functional theory (DFT) calculations were conducted to investigate the correlation of the series of isomeric [Au 13 Ag 12 (PR 3 ) 10 X 8 ] + (X=Cl/Br) clusters, which are mainly differentiated by the coordination mode of the equatorial halides (μ 2 -, μ 3 -and μ 4 -) in the rod-like, bi-icosahedral framework. The theoretical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Li et al. observed Au 13 Ag 12 conformational isomerism controlled by temperature, [30] and subsequent studies showed that the driving force for generating this isomerism arises from changes in the coordination mode of the bridging Cl − ligands [52] . Wang et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Li et al. observed Au 13 Ag 12 conformational isomerism controlled by temperature, [30] and subsequent studies showed that the driving force for generating this isomerism arises from changes in the coordination mode of the bridging Cl − ligands [52] . Wang et al.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination mode of the bridging chalcogen or halogen can induce differences in the geometric structures of the obtained bi‐icosahedral assemblies [52] . Li et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations